2023
DOI: 10.2174/1389203724666230606154719
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose and its Diverse Biological Potential

Eva Sharma,
P.S. Shruti,
Shagun Singh
et al.

Abstract: Trehalose, a disaccharide molecule of natural origin, is known for its diverse biological applications, like in drug development, research application, natural scaffold, stem cell preservation, food, and various other industries. This review has discussed one such diverse molecule ‘trehalose aka mycose’, and its diverse biological applications with respect to therapeutics. Due to its inertness and higher stability at variable temperatures, it has been developed as a preservative to store stem cells, and later,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 126 publications
0
6
0
Order By: Relevance
“…Trehalose, a non-reducing disaccharide, composed of two glucose molecules, serves several functional roles, such as conferring thermostability, providing osmotic protection, storing energy, regulating growth, and participating in sugar signaling [9]. Trehalose metabolism has been associated with cell survival under adverse conditions, making it crucial for stress tolerance in vivo [10][11][12][13]. Exogenous trehalose application enhances a plant's ability to withstand stress related to high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Trehalose, a non-reducing disaccharide, composed of two glucose molecules, serves several functional roles, such as conferring thermostability, providing osmotic protection, storing energy, regulating growth, and participating in sugar signaling [9]. Trehalose metabolism has been associated with cell survival under adverse conditions, making it crucial for stress tolerance in vivo [10][11][12][13]. Exogenous trehalose application enhances a plant's ability to withstand stress related to high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…There are various molecular mechanisms underlying the effects of trehalose [ 65 ]. Trehalose induces autophagy in a mTOR (mechanistic target of rapamycin)-independent manner [ [65] , [66] , [67] ].…”
Section: Introductionmentioning
confidence: 99%
“…There are various molecular mechanisms underlying the effects of trehalose [ 65 ]. Trehalose induces autophagy in a mTOR (mechanistic target of rapamycin)-independent manner [ [65] , [66] , [67] ]. It suppresses the activity of glucose transport proteins on the cell surface, leading to the phosphorylation of the autophagy-initiating kinase ULK1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, over the years, it has been revealed that trehalose may also perform specialized biological functions such as protecting proteins and membranes against various stresses [ 4 , 5 , 6 ]. In recent decades, trehalose has sparked growing interest in a variety of industrial applications, which are mainly attributed to its structural features and its special role in molecular stabilization [ 4 , 7 , 8 ]. It has been widely used in pharmaceuticals, foodstuffs, cosmetics, and agricultural products [ 2 , 4 , 7 ].…”
Section: Introductionmentioning
confidence: 99%